The incremental value of combination copeptin and troponin T for early diagnosis of acute myocardial infarction - Daniel R Mulyono; Arfenda P Mustikawati; Galuh A Tyagitha; Anthony Wijaya; Irna C Wyrahardja; Yoga Yuniadi (The Indonesian Heart Association, 2011)
Background: Copeptin is a protein that is released when the body experiences endogenic stress. The level of copeptin elevated very early and slowly decreases in myocardial infarction. Aim: to determine the incremental value of combination copeptin and troponin T for early diagnosis of Acute Myocardial Infarction.Methods: A search was conducted on PubMed and Cochrane. After screening title and abstract using inclusion and exclusion criteria, three articles were available as full text, but only 2 articles were considered useful by authors and were appraised based on its validity, importance and applicability. The other one article was excluded because the outcome of the study basically differentiates ACS and cardiomyopathy. Results: Both articles showthat the diagnostic value results are not so different. From the first article, a combination of copeptin and troponin T gives the results of sensitivity 87.4%, specificity 66.2%, PPV 46.9%, NPV 93.9%, pre-test probability 21.5%, post-test probability 40.8%, and AUC 0.91. The second article showed a combination of both gave sensitivity values of 98.8%, specificity 77.1%, PPV 46.2%, NPV 99.7%, pre-test probability 16.67%, and post-test probability 46.29%, and AUC 0,97. Conclusion: the combination of troponin T increase the sensitivity of diagnosis of AMI among patients suspected with acute coronary syndrome compared to troponin T alone. The combination of both can be considered as a test to diagnose AMI at early hours.